The Good Grief Devotional : 52 Weeks toward Hope - Christianson, Brent D. (Book collections on Project MUSE., 2019)
The Good Grief Devotional offers wise, honest companionship to those who struggle with the death of a loved one, a divorce, the loss of a job, or another major life transition. Pastor Brent D. Christianson's fifty-two devotions follow the ten stages of grief outlined in Granger Westberg's helpful book Good Grief.